The Influence of Workload, Job Stress, And Work Environment on Employee Performance (Study on Nogo Ikat Weaving in Sanur, Bali, Indonesia) - Maria Yubiliani Laetare Nurak; I Gede Riana (Penerbit Kemala Indonesia, 2023)
Employee performance is one of the company's primary responsibilities in achieving its goals. MSMEs are one of the options available to the community for maximizing their potential. Individuals are more motivated to pursue income due to changing environmental conditions and developing a more advanced economy. Workload, job stress, and the work environment are among the factors that can affect employee performance, especially in the micro- and medium-sized businesses in Sanur that specialize in Nogo ikat weaving. This study seeks to determine how workload, job stress, and work environment impact the performance of Sanur-based Tenun Ikat Nogo employees. This study was conducted at Tenun Ikat Nogo Sanur using a saturation sample to select a sample size of 35 employees. The 5 Likert scale questionnaire was utilized to collect data. The gathered data were then analyzed using multiple linear regression. The findings revealed that employee workload negatively and substantially affects performance. Stress at work has a substantial and negative effect on employee performance. The workplace has a substantial and positive effect on employee performance. This study will provide an empirical contribution regarding the influence of workload, job stress, and work environment on the performance of Tenun Ikat Nogo employees in Sanur. Tenun Ikat Nogo weaving company may consider employee performance-influencing factors such as workload, job stress, and work environment as input or learning references.